Mapping relation between pier settlement and rail deformation of unit slab track system. (October 2020) - Zhou, Wangbao; Nie, Leixin; Jiang, Lizhong; Feng, Yulin; Tan, Zhihua; Chai, Xilin
Abstract: In order to study the effect of the vertical deformation of continuous beam structure of CRTS Ι slab ballastless track on rail deformation, this paper analyzes the mapping mechanism of the structural vertical deformation-rail deformation. Based on the principle of stationary potential energy, the work derives an analytical expression for a mapping between the vertical deformation of continuous beam structure and rail deformation by considering the effect of the subgrade. Then, the mapping relation between the vertical deformation of various typical bridge structures and rail deformation was calculated using analytical method. The results were compared with those obtained using ANSYS finite element method. The effects of four factors on rail deformation were investigated, namely, pier settlement, staggered steps on girder, rotation angles on beam ends, and number of spans of simply supported beam. The calculation results obtained via analytical method and those obtained using finite element method fit well with each other, verifying the rationality and correctness of the analytical method. The expression for analytical method is concise and can easily obtain the mapping relation between the structural vertical deformation and rail deformation using the displacement boundary conditions. The vertical deformation of the rail was proportional to the vertical deformation of same typical structure. Both inside and outside the rail deformation area, the length of rail deformation section did not change with structural vertical deformation. When there were simply supported beams at both ends of the continuous beam, the number of spans of simply supported beams had no significant effect on the rail deformation caused by the vertical deformation of typical continuous beam structures. When there were no simply supported beams, the settlement of side pier of continuous beam caused rail deformation similar to the staggered step of girder.